In Vitro Evaluation of Seagrass Extracts as a Prevention of Microfouling Formation - Keti Fitri; Sri Puji Astuti; Ahmad Jupri; Faturrahman Faturrahman (Jurnal Biologi Tropis, 2022)
Microfouling is the attachment and colonization of bacteria and microalgae on the surface of objects immersed in the sea. So far, the control of biofouling on the surface of marine hulls has been using paints containing Tributylin Organotin (TBT) which have adverse effects on non-target organisms and are not friendly to the environment. The development of environmentally friendly antifouling paint is a solution to overcome the growth of biofouling. This study aimed to evaluate in vitro extract of Thalassia hemprichii as an anti-microfouling agent. Extraction of bioactive from Thalassia hemprichii was carried out by maceration. The filtrate is divided into five kinds of concentration, namely 0%, 25%. 50%, 75%, and 100% were then added to paint A as an anti-microfouling agent. The observed variables were microfouling biomass and the density of bacteria and microalgae attached to the steel plate. The results showed that with increasing concentration applied to the plate caused a decrease in the number of bacteria. The average decrease in each bacterial concentration was 84 x 10^6 CFU/mL, 65 x 10^6 CFU/mL, 41.5 x 10^6 CFU/mL, 28.7 x 10^6 CFU/mL, and 15.8 x 10^6 CFU/mL, respectively. Microalgae attached to the steel plate also experienced a reduction with the average values sequentially being 37 x 10^4 cells/mL, 14 x 10^4 cells/mL, 8 x 10^4 cells/mL, 5 x 10^4 cells/mL, and 2 x 10^4 cells/mL. Likewise, the microfouling biomass on steel plate also decreased in amount with the average values being 99.27 mg, 93.4 mg, 66.43 mg, 59.13 mg and 30.2 mg, respectively. Thus, Thalassia hemprichii extract has the potential to prevent the formation of microfouling.